If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3(2x + -5(6x + 1)) = 2 + 3(x + -11(3x + -8)) Reorder the terms: 6x + 3(2x + -5(1 + 6x)) = 2 + 3(x + -11(3x + -8)) 6x + 3(2x + (1 * -5 + 6x * -5)) = 2 + 3(x + -11(3x + -8)) 6x + 3(2x + (-5 + -30x)) = 2 + 3(x + -11(3x + -8)) Reorder the terms: 6x + 3(-5 + 2x + -30x) = 2 + 3(x + -11(3x + -8)) Combine like terms: 2x + -30x = -28x 6x + 3(-5 + -28x) = 2 + 3(x + -11(3x + -8)) 6x + (-5 * 3 + -28x * 3) = 2 + 3(x + -11(3x + -8)) 6x + (-15 + -84x) = 2 + 3(x + -11(3x + -8)) Reorder the terms: -15 + 6x + -84x = 2 + 3(x + -11(3x + -8)) Combine like terms: 6x + -84x = -78x -15 + -78x = 2 + 3(x + -11(3x + -8)) Reorder the terms: -15 + -78x = 2 + 3(x + -11(-8 + 3x)) -15 + -78x = 2 + 3(x + (-8 * -11 + 3x * -11)) -15 + -78x = 2 + 3(x + (88 + -33x)) Reorder the terms: -15 + -78x = 2 + 3(88 + x + -33x) Combine like terms: x + -33x = -32x -15 + -78x = 2 + 3(88 + -32x) -15 + -78x = 2 + (88 * 3 + -32x * 3) -15 + -78x = 2 + (264 + -96x) Combine like terms: 2 + 264 = 266 -15 + -78x = 266 + -96x Solving -15 + -78x = 266 + -96x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '96x' to each side of the equation. -15 + -78x + 96x = 266 + -96x + 96x Combine like terms: -78x + 96x = 18x -15 + 18x = 266 + -96x + 96x Combine like terms: -96x + 96x = 0 -15 + 18x = 266 + 0 -15 + 18x = 266 Add '15' to each side of the equation. -15 + 15 + 18x = 266 + 15 Combine like terms: -15 + 15 = 0 0 + 18x = 266 + 15 18x = 266 + 15 Combine like terms: 266 + 15 = 281 18x = 281 Divide each side by '18'. x = 15.61111111 Simplifying x = 15.61111111
| 6x^2-18x-243=0 | | 5*x+x=180 | | 7x=5(x+18) | | 6x+3(2x-5(x+1))=2+3(x-11(3x-8)) | | 1.3x+6y=16 | | sqrtx-1-3=9 | | 1.3-0.02= | | -20x+4=3x | | x+y+16+3=345 | | x+y+16+3=435 | | log(x+13)-log(2)=log(5x+4) | | 4y^2+81=36x | | ln(1000x)=1 | | g(x)=4*0.8 | | 2x+3-3x=9 | | 5n+7=n-1 | | 2x^2-29x=-7x^2-3x-16 | | X^4+2x^3-8=0 | | f(x)=4x^2+7x-5 | | 9y+5-6y=11 | | 5r+10r=135 | | 5x-1+8x+90=180 | | -41+r=46 | | fx=4x^2+7x-5 | | 5x-1+8x= | | 0.125x=-17 | | 110+8x=119+7x | | 5(h+2)=3(h-2) | | 4+78x=52x+28 | | 3x+5(5x-1(3x-2))=5-8(2x+7(x-6)) | | 9y-1=0 | | 15-v=239 |